Intergenerational Relations (IntechOpen, 2024)
Intergenerational Relations - Contemporary Theories, Studies, and Policies, concentrates on actual discussions around various aspects of interactions that occur between people from different age groups and generations. The authors present studies related to four sets of challenges crucial for relationships between children, young adults, middle-aged adults, and older adults. These challenges include social and cultural challenges, economic and technological challenges, environmental challenges, and political and legal challenges. The volume also addresses issues important for the global, national, regional, and local application and performance of intergenerational solutions, projects, and programs focused on achieving the United Nations Sustainable Development Goals (SDGs). The collection includes chapters encompassing research and practical recommendations from various disciplines such as demography, economics, ethics, management, gerontology, public health, pedagogy, social work, political science, and sociology. This book is an asset to academic and professional communities interested in theories of intergenerational relationships as well as public services and age-related policies. Moreover, the volume is a useful resource to help students, practitioners, and people working in government, business, and nonprofit organizations build positive and harmonious interactions between generations.